Atypical Presentation of a Type 2 Endoleak following Emergency Open Repair of a Ruptured Abdominal Aortic Aneurysm. (2016) - Sharma, K.; Halandras, P.; Milner, R.
Abstract : Background: An endoleak is a common complication following EVAR. Specifically, a Type 2 endoleak occurs because of retrograde flow from lumbar vessels outside the endograft within the aneurysm sac. Even though it is common following EVAR, it has not been identified as a complication following open ruptured abdominal aortic aneurysm (AAA) repair. Report: A 73-year-old male underwent open repair of a ruptured AAA. Five months later, computed tomography revealed filling from a lumbar vessel mimicking a Type 2 "endoleak." The initial ultrasound showed a single pair of lumbar vessels with aneurysm sac expansion 8 weeks later. The "endoleak" and expanding sac were treated, and the 2-year surveillance demonstrated sac shrinkage. Discussion: Because endoleak is a complication after EVAR, this case provides a unique presentation of Type 2 "endoleak" physiology following open repair of a ruptured AAA. It is believed that it is necessary to expand the list of possible complications after open ruptured AAA repair to include "endoleaks." Highlights: An endoleak is a common complication observed after EVAR, but not open AAA repair. Type 2 endoleak after open AAA repair has a similar treatment paradigm to EVAR. Translumbar embolization done utilized bony landmarks without endograft as landmark. Endoleak is a complication of EVAR, but open AAA repair can mimic similar pathology.